Is cytomegalovirus a risk factor for haemorrhagic cystitis in allogeneic haematopoietic stem cell transplantation recipients?. Issue 8 (November 2018) - Atilla, Erden; Yalciner, Merih; Atilla, Pinar Ataca; Ates, Can; Bozdag, Sinem Civriz; Yuksel, Meltem Kurt; Toprak, Selami Kocak; Gunduz, Mehmet; Ozen, Mehmet; Akan, Hamdi; Demirer, Taner; Arslan, Onder; et al.
Background: Haemorrhagic cystitis (HC) is usually a serious complication in allogeneic haematopoietic stem cell transplantation (allo-HSCT) recipients. In this study, our aim was to define risk factors and outcomes for patients with HC in an allo-HSCT setting. Methods: We retrospectively evaluated 249 allo-HSCTs performed between 2011 and 2016 in our centre. Results: HC was diagnosed in 98 patients (39%) at a median of 119 days (range 5–580) and 91 (93%) of the patients had late onset disease. In univariate analysis, HC was related to cytomegalovirus (CMV) reactivation ( P <0.001) and BK viraemia ( P <0.001); in multivariate analysis, the presence of CMV reactivation was determined to be an independent risk factor (odds ratio: 22.1; 95% CI 1.73, 282.44; P =0.017). There was no association detected between acute graft versus host disease and patients diagnosed with HC within 100 days of transplant. HC was significantly increased by the presence of myelo-ablative conditioning (odds ratio: 31.28; 95% CI 3.98, 246.87; P =0.001) and BK viraemia (odds ratio: 3.93; 95% Cl 1.10, 14.05; P =0.035) in patients with HC grade II and beyond. Forced hydration was recommended in all patients with grade I HC. Patients with HC and clots were treated with continuous bladder irrigation, and 14 of 44 patients with BK viraemia received cidofovir ± ribavirin. Eight of these patients (57%) responded to treatment. Refractory HC was detected in 17 patients (17%) and resolved by a variety of procedures. Conclusions: This study suggests that CMV reactivation is associated with increased risk of HC in multivariate analysis, however, this result is not confirmed in patients with HC grade II and beyond.